Gambaran Penerapan Pecking Order Theory Pada PT. Indofood CBP Sukses Makmur, Tbk - Putri Aprilliya; Puja Firmasari; Catur Rahayu Novratiwi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to provide an overview of the implementation of capital structure policies based on the Pecking Order Theory (POT) at PT. Indofood CBP Sukses Makmur, Tbk., one of the manufacturing companies listed on the Indonesia Stock Exchange. The research employs a descriptive quantitative approach to assess the company’s financing patterns over time. The sample was selected using a purposive (non-probability) sampling method, deliberately chosen based on data feasibility, including relevance, availability, and completeness of indicators required to examine the hierarchy of the POT. The company’s financing decisions were analyzed using annual financial statements from 2016 to 2024, considering several variables such as Growth, Profitability, Debt to Asset Ratio (DAR), and Retained Earnings. According to the Pecking Order Theory, firms prefer to finance investments first with internal funds (retained earnings), followed by debt, and lastly through equity issuance. The descriptive analysis results show that the financing pattern implemented by PT. Indofood CBP Sukses Makmur, Tbk. consistently aligns with the hierarchy proposed by the Pecking Order Theory. The company tends to rely primarily on internal funds before resorting to debt and new equity issuance. These findings provide strong empirical evidence supporting the validity of the Pecking Order Theory in explaining corporate financing decisions and their implications for capital structure.